Effects of pH and light exposure on the survival of bacteria and their ability to biodegrade organic compounds in clouds: implications for microbial activity in acidic cloud water - Y. Liu; Y. Liu; C. K. Lim; Z. Shen; P. K. H. Lee; P. K. H. Lee; T. Nah; T. Nah; T. Nah (Atmospheric Chemistry and Physics, 2023)
Recent studies have reported that interactions between live bacteria and organic matter can potentially affect the carbon budget in clouds, which has important atmospheric and climate implications. However, bacteria in clouds are subject to a variety of atmospheric stressors, which can adversely affect their survival and energetic metabolism and, consequently, their ability to biodegrade organic compounds. At present, the effects of cloud water pH and solar radiation on bacteria are not well understood. In this study, we investigated how cloud water pH (pH 3 to 6) and exposure to solar radiation impact the survival and energetic metabolism of two Enterobacter bacterial strains that were isolated from ambient air collected in Hong Kong and their ability to biodegrade organic acids. Experiments were conducted using simulated sunlight (wavelength from 320 to 700 nm) and microcosms comprised of artificial cloud water that mimicked the pH and chemical composition of cloud water in Hong Kong, South China. Our results showed that the energetic metabolism and survival of both strains depended on the pH. Low survival rates were observed for both strains at pH<4, regardless of whether the strains were exposed to simulated sunlight. At pH 4 to 5, the energetic metabolism and survival of both strains were negatively impacted only when they were exposed to simulated sunlight. Organic compounds such as lipids and peptides were detected during exposure to simulated sunlight at pH 4 to 5. In contrast, there were minimal effects on the energetic metabolism and the survival of both strains when they were exposed to simulated sunlight at pH>5. The biodegradation of organic acids was found to depend on the presence (or absence) of simulated sunlight and the pH of the artificial cloud water medium. Overall, this study provides new insights into how two common atmospheric stressors, cloud water pH and exposure to solar radiation, can influence the survival and energetic metabolism of bacteria, and consequently the roles that they play in cloud processes.